2008
DOI: 10.2190/ec.39.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Students Evaluating Internet Sources: From Versatile Evaluators to Uncritical Readers

Abstract: The Internet is a significant information resource for students due to the ease of access it allows to a vast amount of information. As the quality of the information on the Internet varies, it is important that students are able to evaluate such information critically. The aim of the study was to investigate how students evaluate Internet sources in an authentic learning task. Upper secondary school students (n = 25) were asked to look for source material on the Internet in order to write an essay. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 26 publications
6
48
1
6
Order By: Relevance
“…Findings from the present study are consistent with results from other work showing that when students read for information on the Internet, they are more concerned with content relevance than with credibility; they rarely attend to source features to evaluate reliability and author perspective; and when they do refer to source features in their explanations, judgments about the quality of sources are often vague, superficial, and characterized by a lack of reasoned justification (see Barzilai & Zohar, ; Britt & Aglinskas, ; Kiili et al., ). It is important to note that few of these previous studies were conducted with middle school students.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Findings from the present study are consistent with results from other work showing that when students read for information on the Internet, they are more concerned with content relevance than with credibility; they rarely attend to source features to evaluate reliability and author perspective; and when they do refer to source features in their explanations, judgments about the quality of sources are often vague, superficial, and characterized by a lack of reasoned justification (see Barzilai & Zohar, ; Britt & Aglinskas, ; Kiili et al., ). It is important to note that few of these previous studies were conducted with middle school students.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research outlines the shortcomings of high school and college students when evaluating Internet sources (e.g., Goldman et al., ; Kiili, Laurinen, & Marttunen, ; S. Zhang & Duke, ), but only a few studies have focused on adolescent learners’ evaluation practices. These studies suggest that adolescents rarely question the accuracy of information (e.g., Barzilai & Zohar, ; Walraven, Brand‐Gruwel, & Boshuizen, ; M. Zhang, ).…”
mentioning
confidence: 99%
“…In contrast to their reported awareness and concerns about information quality, adolescents’ actual evaluation behavior seems to be unsystematic and sometimes inconsistent. A number of studies have shown that when they search for information online, adolescents tend to skim rather than read webpages, to rely on known sources, and to prioritize easiness of use over content quality (Brand‐Gruwel et al., ; Foss et al., ; Gasser et al., ; Julien & Barker, ; Kiili, Laurinen, & Marttunen, ; Watson, ; Zhang, ). Watson () characterized this type of behavior as convenience and pragmatism.…”
Section: Adolescents’ Awareness Of Information Qualitymentioning
confidence: 99%
“…Exempelvis, i en studie där gymnasieelever fick "tänka-högt" kring hur de går till väga vid sökning av information, visade det sig att de främst utvärderade innehållets relevans för uppgiften och bortsåg från avsändaren (Kiili, Laurinen, & Marttunen, 2008). I en senare studie av Bråten, Strømsø och Andreassen (2016) fann författarna att när universitetsstudenter (n=259) skulle fatta beslut i hälsorelaterade frågor utifrån läsning av multipla dokument så undlät de att utvärdera innehållslig information med hjälp av tillgänglig källinformation och förlitade sig istället på personliga erfarenheter.…”
Section: Läsning I Informationssamhälletunclassified